Application of Learning Management Test Instruments To Identify Questions As Evaluation Tools - Hayat, Abdul; Azizah, Nur; Nur Rizqi, Amalia (Pandawan, 2018)
In the era of disruptive 4.0, the process of education in management at Higher Education was held in various forms such as formal education and non-formal education. In addition, the application of learning management as an evaluation tool also aims to find and find various factors that lead to the success and failure of students after following the education process, so that a bright spot will be found as a way out for improvement in the implementation of education in the future. This study discusses the notion of tests, the development of tests as an evaluation tool, true-false tests, multiple choice tests, various forms of multiple choice tests, matching tests, matching tests (completion test). ), and short answer questions. Therefore, it isnecessary to conduct an analysis of the instrument for making the items that have been made by management at the University in evaluating their students. With the hope that the question analysis aims to identify the questions that are good, not good, and questions that are not feasible. Given to students.